Evaluation of an activated carbon-based deactivation system for the disposal of highly abused opioid medications. (2nd January 2018) - Gao, Xinyi; Bakshi, Pooja; Sunkara Ganti, Sindhu; Manian, Mahima; Korey, Andrew; Fowler, William; Banga, Ajay K.
Abstract: Context: The improper disposal of unused prescription opioids has a potential for abuse as well as environmental contamination. Consequently, there is an imperative need for an environmentally safe, convenient, and effective drug disposal system. Objective: The objective of this study is to analyze the deactivation efficiency of the disposal system employing four model opioid drugs of high abuse potential. Methods: The deactivation system used in this investigation is an activated granular carbon based disposal system in the form of a pouch, which can be used to safely and effectively deactivate unused or expired medications. HPLC method validation for each drug was performed prior to analyzing drug content in the deactivation study. Opioid drugs in different dosage forms were added to individual pouches in the presence of warm water. Pouches were shaken and sealed, then stored at room temperature. The deactivation efficiency of the system was tested by collecting samples at different time points up to 28 d. Results: An average of 98.72% of medications were adsorbed by activated carbon within 8 h and continued to do so over time. At the end of the 28-d study, more than 99.99% of all drugs were deactivated. In the desorption study, almost no drug leached out from the activated carbon in larger volume of water and less than 1.3% leached out on extraction with ethanol. Conclusion: This unique drug disposal system successfully adsorbed and deactivated the model opioid medications by the end of 28 d, offering a safe and convenient route of disposal of unused or residual opioid drugs.